National Innovation System and Curriculum Development in Business Education Incorporating Technology & Innovation Management Systems - Razzaq, Faryal; Ashfaq, Sana; Ashfaq, Muhammad bin (Journal of Peace, Development and Communication, 2022)
Malcom X said, “And just because you have colleges and universities, doesn't mean you have education”. Higher Education Institutions (HEIs) in Pakistan suffer from several systemic deficiencies. As a result, it continues to provide graduates that are unemployable, despite emerging shortages of skilled manpower in an increasing number of sectors. Specifically, the unemployment rate of business graduates is alarming. Adoption of technology and ICT tools in higher education is an essential component of andragogy – the motivation to innovate is also fundamentally linked to the cultural influences on higher education. National Innovation System (NIS) links together the public, private and academic sector and utilizing NIS to facilitate the cultural innovation in education would ensure a stable economic growth. The changing state of the financial crises and the post-pandemic world begs the educational landscape to employ innovative solutions and make use of intellectual capital to ensure that graduates have the skills and resources necessary to enter their careers. Research-based education in business schools in Pakistan has the potential to achieve a higher standard of scholarship stemming from national level issues but lack of funding and motivation to compete with globalization may deter these efforts. The largest factor in achieving Technology and Innovation Management (TIM) is applying ICT and Instructional Design (ID) tools to innovate and stay in competition with the andragogic challenges of the post-pandemic world.